Postbiotic supplementation promotes gut barrier integrity and immune balance in cats via microbiota modulation - Wang, Weiwei; Miao, Chengyi; Chen, Qianqian; Wang, Longjiao; Chang, Xiaohan; Zhao, Lili; Ma, Wenjing; Lei, Shanyu; Ma, Mengyao; Zhang, Yuqiang; Chen, Shuxing; Chen, Lishui; et al. (Frontiers in Microbiology, 2025)
IntroductionGastrointestinal disorders are common in cats and are closely linked to the gut microbiota, which supports immune function, metabolic balance, and barrier integrity. Although probiotics are beneficial, they can be unstable in pet foods. Postbiotics offer a safer and more stable alternative.MethodsA postbiotic derived from Bifidobacterium animalis subsp. lactis was prepared by heat inactivation (95°C, 30 min), followed by centrifugation and freeze-drying. Eighteen healthy domestic cats were randomly assigned to a control group, a low-dose postbiotic group, or a high-dose postbiotic group for 28 days. Assessments included physical condition, immune status, gut barrier function, microbiota composition, and fecal short-chain fatty acids (SCFAs).ResultsPostbiotic supplementation improved fur condition and enhanced gut barrier integrity, as indicated by reduced levels of permeability markers such as diamine oxidase (DAO) and lipopolysaccharide (LPS). It also promoted immune function by increasing serum immunoglobulin G and anti-inflammatory cytokines IL-10 and IL-4. In addition, the intervention enriched beneficial bacteria such as Bifidobacterium spp. and elevated fecal concentrations of key SCFAs, including acetic, propionic, and butyric acids.DiscussionThese findings support the use of postbiotics as a safe and effective nutritional approach to help maintain gastrointestinal and immune health in cats.